2015
DOI: 10.1016/j.brat.2014.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of cognitive behavior treatment for pediatric obsessive-compulsive disorder: Acute outcomes from the Nordic Long-term OCD Treatment Study (NordLOTS)

Abstract: This study was registered in Current Controlled Trials; Nordic Long-term Obsessive-compulsive disorder (OCD) Treatment Study (www.controlled-trials.com ISRCTN66385119).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(69 citation statements)
references
References 52 publications
6
56
0
6
Order By: Relevance
“…In the remaining sessions, children and adolescents were treated individually for 45 minutes, and then the parents were seen with or without the child for the remaining 30 minutes. 21 Assessments were conducted at baseline, midtreatment (week 7), and posttreatment (week 14) by certified independent evaluators (IEs). At the end of the 14 weeks of treatment, participants were rated as either responders or nonresponders, based on the CY-BOCS total score.…”
Section: Methods Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the remaining sessions, children and adolescents were treated individually for 45 minutes, and then the parents were seen with or without the child for the remaining 30 minutes. 21 Assessments were conducted at baseline, midtreatment (week 7), and posttreatment (week 14) by certified independent evaluators (IEs). At the end of the 14 weeks of treatment, participants were rated as either responders or nonresponders, based on the CY-BOCS total score.…”
Section: Methods Participantsmentioning
confidence: 99%
“…A detailed description of the demographic and clinical characteristics of the NordLOTS study sample has been reported elsewhere. 21 To be eligible to participate in the study, participants had to be between 7 and 17 years of age, to receive a primary DSM-IV diagnosis of OCD, and to have a baseline CY-BOCS score of !16. Exclusion criteria were the presence of psychiatric disorder(s) with a higher treatment priority (e.g., psychosis or major depression disorder), or a pervasive developmental disorder (i.e., PDD, Asperger's disorder, or autism spectrum disorder).…”
Section: Methods Participantsmentioning
confidence: 99%
“…30 The first 60 minutes of each session were devoted to exposure and response prevention (ERP) and cognitive restructuring with the child; the remaining 30 minutes were family-focused. Following an approach validated in previous work, 19,31 each week covered a different topic including causes and prevalence of OCD; the rationale for ERP; the importance of disengaging from symptoms; and the range of emotional responses to OCD. In addition to psychoeducation, parents received a detailed review of the child session and what was assigned for homework, and they had an opportunity to ask questions.…”
Section: Methodsmentioning
confidence: 99%
“…High rates of comorbidity ranging from 25 to 65% have been reported in both clinical and epidemiological studies [19][20][21][22]. Common comorbid conditions include major depression (10-73%) and anxiety disorders (26-76%) [6,7,10,14].…”
Section: Introductionmentioning
confidence: 99%